MANAJEMEN BUDAYA MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH RIFA'IYAH LIMPUNG BATANG - Mukh Khusnaini; Asma’ul Husna (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze and describe in depth the management of educational quality culture implemented at Madrasah Ibtidaiyah (MI) Rifa'iyah Limpung Batang, as well as to identify the factors that support and hinder its implementation. Specifically, the objective is to understand how the planning, organizing, implementing, and evaluating of quality management are carried out to create a superior and sustainable academic culture within the madrasah. The method used in this research is qualitative with a case study approach. Data collection was conducted through in-depth interviews with the headmaster, teachers, and the school committee, as well as participatory observation of teaching-learning activities and school culture, and documentation. Data were analyzed using data reduction, data display, and conclusion-drawing techniques. The results show that MI Rifa'iyah Limpung Batang has successfully built a quality culture through four main pillars: (1) Strong leadership commitment to quality; (2) Regular implementation of competency improvement programs for teachers and staff; (3) Active involvement of all stakeholders (teachers, students, parents, and the community) in the quality assurance process; and (4) The habituation of religious values and discipline as the foundation of school culture.